2020
DOI: 10.1016/j.contraception.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of immediate postpartum long-acting reversible contraception: A qualitative study,

Abstract: Objectives: The objective of this study was to explore perceptions and experiences of immediate postpartum long-acting reversible contraception (LARC) counseling and decision-making, with a focus on reproductive autonomy. We aimed to assess the potential for reproductive coercion. Study design: This was a qualitative study using semi-structured interviews with Spanish and English speaking women who received an intrauterine device or contraceptive subdermal implant immediately postpartum. They were recruited be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…In addition, it was stated that women prefer accurate information available from the antenatal period to give them more time to ask questions and think about decisions to be made. 16 The educational process in early labor is a less than optimal choice in convincing the mother and husband or other family members to choose the right contraceptive method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was stated that women prefer accurate information available from the antenatal period to give them more time to ask questions and think about decisions to be made. 16 The educational process in early labor is a less than optimal choice in convincing the mother and husband or other family members to choose the right contraceptive method.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be that providers are differentially recommending LARC to patients of color (Dehlendorf et al, 2010). Indeed, recent qualitative research from unbundling states documents concerning reportsdlargely from racially minoritized patientsdof undue pressure to use IPP LARC (Mann, White, Rogers, & Gomez, 2019;Sznajder, Carvajal, & Sufrin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study in the United States found that many abortion clients felt pressured to adopt a particular contraceptive method, usually an IUD or implant 10 . Similarly, interviews with postpartum people revealed that they experienced pressure from providers to immediately initiate use of a LARC 11 . In Sub‐Saharan Africa, people participating in a family planning program reported experiencing a range of coercive practices, including provision without consent and refusal to remove IUDs and implants 12 …”
mentioning
confidence: 99%
“…10 Similarly, interviews with postpartum people revealed that they experienced pressure from providers to immediately initiate use of a LARC. 11 In Sub-Saharan Africa, people participating in a family planning program reported experiencing a range of coercive practices, including provision without consent and refusal to remove IUDs and implants. 12 Contraceptive counseling strategies may range from directive approaches, such as tiered-eff ectiveness counseling, to an informed choice model in which the provider focuses on presenting objective, nonjudgmental information so that patients can select the method that best satisfi es their personal needs and preferences.…”
mentioning
confidence: 99%